Example pygmy blue whale calls from Marine soundscape variation reveals insights into baleen whales and their environment: a case study in central New Zealand - Victoria E. Warren; Craig McPherson; Giacomo Giorli; Kimberly T. Goetz; Craig A. Radford (2021)
.wav file containing pygmy blue whale calls. Data collected by NIWA, New Zealand, at the South Taranaki Bight recording location, 16th July 2016.